Sprouting, Survival and Growth of Young Sugarcane (Saccharum officinarum L.) Treated with Diazotrophic Bacteria (Gluconacetobacter diazotrophicus) [RESEARCH NOTE] - de la Cruz, Christian Paul P. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2012)
Sprouting, survival and growth of young sugarcane (Saccharum officinarum L. var. VMC-86-550) treated with the nitrogen-fixing endophyte Gluconacetobacter diazotrophicus was investigated. Nine treatments were laid out in a split-plot design with three levels of microbial concentration (108, 1010 and 1012 cells mL-1) for the main plot and three methods of inoculation (spraying, soaking and dipping) for the subplot. Inoculated plants showed significant increase in % survival, plant height and shoot/root biomass compared with the uninoculated control at 45 d after planting (DAP). However, no significant differences were observed in % sprouting between inoculated plants and the uninoculated control at 30 DAP. Introduction of the microbial inoculant at 1012 cells mL-1 by means of the dipping method had constantly yielded taller plants with greater shoot and root biomass relative to the other treatments and the uninoculated control. Interaction effects of the dipping method and 1012 cells mL-1 of microbial concentration might have delivered optimum amount of bacteria into the setts, hence, significant improvement in growth parameters of the resulting plantlets. This experiment shows the potential use of G. diazotrophicus in the development of a cost-effective technology in sugarcane production.